Awards: Mr. Shamsul Bahrain Gulam Ali - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
Congratulation to Mr. Shamsul Bahrain Gulam Ali who received the Open and Distance Learning (ODL) 2020 Award in recognition of his contribution to open and distance learning on 10 September 2020.